2016
DOI: 10.1021/jacs.5b11657
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Kinetics Correlations in Isostructural Crystals of α-(ortho-Tolyl)-acetophenones: Pinning Down Electronic Effects Using Laser-Flash Photolysis in the Solid State

Abstract: Aqueous suspensions of nanocrystals in the 200-500 nm size range of isostructural α-(ortho-tolyl)-acetophenone (1a) and α-(ortho-tolyl)-para-methylacetophenone (1b) displayed good absorption characteristics for flash photolysis experiments in a flow system, with transient spectra and decay kinetics with a quality that is similar to that recorded in solution. In contrast to solution measurements, reactions in the solid state were characterized by a rate limiting hydrogen transfer reaction from the triplet excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…However, it is known that the spectroscopic analyses of crystals and bulk powders is complicated by their high optical densities, strong light scattering, and the potential interference by the accumulation of photoproducts. To address these challenges, our group has developed a flow method that uses nanocrystals suspended in a nondissolving fluid such as water. We have shown that low-loading suspensions of crystals in the ca. 50–500 nm size range are suitable for transmission spectroscopy because of their homogeneous illumination and reduced light scattering.…”
mentioning
confidence: 99%
“…However, it is known that the spectroscopic analyses of crystals and bulk powders is complicated by their high optical densities, strong light scattering, and the potential interference by the accumulation of photoproducts. To address these challenges, our group has developed a flow method that uses nanocrystals suspended in a nondissolving fluid such as water. We have shown that low-loading suspensions of crystals in the ca. 50–500 nm size range are suitable for transmission spectroscopy because of their homogeneous illumination and reduced light scattering.…”
mentioning
confidence: 99%
“…), stable suspensions of crystalline particles with an average size in the submicrometer regime can be prepared. We term such mixtures nanocrystalline suspensions, which have been shown to be amenable to spectroscopic analysis using standard solution-phase methods. , For each derivative, nanocrystalline suspensions were prepared using a 0.04 mM CTAB surfactant solution and stock solutions in acetonitrile. For ketone 4 , 0.2 mL of a 2.5 mg/mL acetonitrile solution was added dropwise to ∼20 mL of a vortexing surfactant solution.…”
Section: Resultsmentioning
confidence: 99%
“…Laser flash photolysis experiments were performed with an excimer laser (308 nm, 17 ns pulse width). [9] An anocrystalline suspension of azide 1 was prepared by following the reprecipitation technique described by Simoncelli et al [5] As olution of azide 1 (0.7 mm,2 00 mL) in acetone was slowly injected into 10 mL of Millipore water.T he resulting suspension was sonicated three times at room temperature for 6min, allowing 3min rest between each run. The absorbance of the resulting nanocrystalline suspensions was between 0.3 and 0.5 at 308 nm.…”
Section: Laser Flash Photolysismentioning
confidence: 99%
“…[3a, 4] Because solid-statep hotoreactions cannot always be sufficiently explained by crystal structure/reactivity correlations, Garcia-Garibay and co-workers developed at echnique using laser flash photolysis of nanocrystalline suspensions to detect excited states and reactive intermediates within crystal lattices. [5] This approach makes it possible to elucidate the mechanisms of solid-state photoreactions based on spectroscopy.…”
Section: Introductionmentioning
confidence: 99%